Are there neuromuscular differences on proximal and distal joints in patellofemoral pain people? A systematic review and meta-analysis. (June 2022) - Rodrigues, Rodrigo; Daiana Klein, Kelli; Dalcero Pompeo, Klauber; Aurélio Vaz, Marco
Abstract: We aim to determine the neuromuscular differences in proximal and distal joints between patellofemoral pain (PFP) and healthy participants. Relevant articles were selected through seven databases. Studies comparing electromyography (EMG) or morphology parameters of trunk, hip, ankle/foot joints in PFP people compared to a healthy control group (CG) were included. 1458 studies were identified, from which 36 were included in the systematic review [PFP, n = 655; CG, n = 649] (31 involving EMG) and 32 in the meta -analysis (27 involving EMG). 75% of studies presented moderate to high methodological quality. The meta -analysis demonstrated that, compared to CG, PFP have: (i) similar transversus abdominis/internal oblique and erector spinae muscle onset, independently of sex; (ii) similar EMG amplitude of gluteus medius and gluteus maximus, independently of sex or task performed; (iii) similar gluteus medius muscle onset, independently of sex or task performed; (iv) similar gluteus maximus muscle onset, independently of sex; (v) a small effect for a shorter activation duration of gluteus medius (0.50; 95% CI [0.07; 0.93]; p = 0.02); (vi) a medium effect for a shorter activation duration of gluteus medius during stair/step down task (0.81; 95% CI [0.18; 1.45]; p = 0.01); (vii) similar external oblique, gluteus maximus, tensor fascia latae, tibialis anterior and fibularis muscle thickness and (viii) a small effect for a smaller gluteus medius muscle thickness (0.52; 95% CI [0.22; 0.82]; p = 0.007). We were not able to perform meta -analysis for EMG at distal joints. Neuromuscular differences in PFP seems to occur only in the gluteus medius muscle. Due to high heterogeneity and several methodological concerns observed, mainly in EMG studies, the interpretation of these results needs caution.